QUALITATIVE STUDY TO EXPLORE PERCEPTION OF STRUGGLERS IN MEDICAL COLLEGE - Naseer Alam Tariq (Army Medical College Rawalpindi, 2019)
This article presents the finding of interviews to explore perception of strugglers in Medical Collage. Aim of study was to acquire into those circumstances which drive strugglers into Medical Collages short of their goals leading towards failures. Utilizing the qualitative research design information was gathered through classroom observations and student interviews. Improved understanding of what motivates students will prompt them to modify their strategy so as to foster self-directed efforts towards their goals. Students who lack motivation intermixes intellectual ability, content knowledge, emotional stamina and goal striving with diverse learning environments. Attributional retraining (AR) is a motivation-enhancing treatment designed to offset the dysfunctional explanatory thinking that can arise from lack of motivation, lame excuses often raised by students of their failure and unsatisfactory learning experiences. The theme includes academic performance, failure and motivation level which translate academic efforts into strugglers perception.